Evaluating the impact of the Community Helpers Program on adolescents 12–18 years old in Edmonton, Canada - Pulok, Mohammad Habibullah; Novaes de Amorim, Arthur; Johansen, Sandra; Pilon, Kristin; Lucente, Christina; Saini, Vineet (Canadian journal of public health, 2024)
Intervention Alberta Health Services (AHS) Community Helpers Program (CHP) to enhance mental health among youth. Research question Identifying the impact of CHP on mental illness–related acute care use among adolescents aged 12–18 years in Edmonton and determining cost avoidance. Methods Using administrative data from AHS, public school catchment area data from the Edmonton Public School Board, and area-level socioeconomic deprivation status indicators from the Pampalon deprivation index, we applied geographical regression discontinuity design to estimate the effect of CHP implementation on depression-, anxiety-, and suicide-related acute care use (emergency department visits and inpatient admissions). Cost data were derived from Interactive Health Data Application of Alberta Health. The study period (2002–2022) included pre (2002–2011) and post (2012–2020) CHP implementation periods. Results CHP had statistically significant impact when distance from the boundary (catchment area identifier to divide the sample into treated and control groups) was between 600 and 800 m. About 90 and 80 fewer anxiety- and depression-related visits (per 1000 visits) were observed among individuals aged 12–15 and 16–18 years, respectively, in catchment areas of the public schools where CHP was implemented. Impact of CHP on suicide-related visits was only statistically significant among individuals aged 12–15 years. Annual cost reduction ranged from $161,117 to $269,255 for anxiety- and depression-related visits. Conclusion Findings show contextual effect of CHP; i.e., being potentially exposed to the program reduced the likelihood of anxiety- and depression-related visits. Costs of CHP implementation could be compared with the avoided costs to assess economic benefits of implementing CHP.